Inhibition of Cell Proliferation and Growth of Pancreatic Cancer by Silencing of Carbohydrate Sulfotransferase 15 In Vitro and in a Xenograft Model - Takakura, Kazuki; Shibazaki, Yuichiro; Yoneyama, Hiroyuki; Fujii, Masato; Hashiguchi, Taishi; Ito, Zensho; Kajihara, Mikio; Misawa, Takeyuki; Homma, Sadamu; Ohkusa, Toshifumi; Koido, Shigeo (PloS one, 2015)
Chondroitin sulfate E (CS-E), a highly sulfated glycosaminoglycan, is known to promote tumor invasion and metastasis. Because the presence of CS-E is detected in both tumor and stromal cells in pancreatic ductal adenocarcinoma (PDAC), multistage involvement of CS-E in the development of PDAC has been considered. However, its involvement in the early stage of PDAC progression is still not fully understood. In this study, to clarify the direct role of CS-E in tumor, but not stromal, cells of PDAC, we focused on carbohydrate sulfotransferase 15 (CHST15), a specific enzyme that biosynthesizes CS-E, and investigated the effects of the CHST15 siRNA on tumor cell proliferation in vitro and growth in vivo. CHST15 mRNA is highly expressed in the human pancreatic cancer cell lines PANC-1, MIA PaCa-2, Capan-1 and Capan-2. CHST15 siRNA significantly inhibited the expression of CHST15 mRNA in these four cells in vitro. Silencing of the CHST15 gene in the cells was associated with significant reduction of proliferation and up-regulation of the cell cycle inhibitor-related gene p21CIP1/WAF1. In a subcutaneous xenograft tumor model of PANC-1 in nude mice, a single intratumoral injection of CHST15 siRNA almost completely suppressed tumor growth. Reduced CHST15 protein signals associated with tumor necrosis were observed with the treatment with CHST15 siRNA. These results provide evidence of the direct action of CHST15 on the proliferation of pancreatic tumor cells partly through the p21CIP1/WAF1 pathway. Thus, CHST15-CS-E axis-mediated tumor cell proliferation could be a novel therapeutic target in the early stage of PDAC progression.